Customer Loyalty Factors Influence On Pt. Bank Sul Selbar Main Branch Makassar - Utina, Dian Anggriani; parenden, Adrianus; Junaidin, Junaidin (STIE AMKOP, 2024)
Introduction Factors influencing customer loyalty In the era of globalization, business competition between companies is very tight on customer loyalty due to the bank's image in the eyes of society, services are reluctant to switch. Problem. bank image, trust, shared service. Quantitative method, measurement obtained through a questionnaire. Population, customers of PT. Bank Sulselbar Makassar Branch totaled 2,594 people. purposive sample. Multiple linear regression analysis of the path analysis model tests the effect of bank image (X1), trust (X2), service (X3), on customer satisfaction (Y1) customer loyalty (Y2). Testing the independent variables on the dependent variable is the F test. Statistical results Fcount = 17,338 >Ftable = 2.704. significance 0.05, conclusion, significant between bank image, customer trust, service to customer satisfaction. coefficient value of 0.273, customer trust. 0.223. service has a regression coefficient. 0.297, the most dominant influence customer service satisfaction PT. Bank Sulselbar Makassar Branch. Keywords: Factors, Loyalty, Customers, bank